Geometrical Characteristics of Fixed Mirror Distributed Focus Solar Concentrator, Serdang, Malaysia - Ng, Khai Mun (2011)
Fixed mirror distributed focus (FMDF) solar concentrator is a solar thermal concentrating system means to collect solar energy for sustainable power generation. The FMDF collector consists of a stationary spherical reflector and a moveable solar receiver with tracking mechanism. There is limited investigation on collector performance on a specific local point of solar receiver in daytime basis under tropics skies. In the present work, a detailed numerical modelling was developed to assess the collector as the first objective. The dimension reference of the simulation model was formulated based on the Universiti Putra Malaysia Solar Bowl. Mathematical models of reflection characterisation of the reflector, radiation interception, collector concentration ratio profile, solar flux density and radiation contour mapping were resolved in a segregated manner using MATLAB programming environment. A proposed model was introduced to investigate the collector performance numerically in daytime basis; to predict the overall solar flux concentration along the receiver in time domain. The model has been enhanced by adopting the actual measurement o solar radiation data to predict the collector performance. As the second objective, a model FMDF collector was fabricated according to the geometry modelling executed in simulations. An outdoor experimental study was conducted in daytime operation located at Serdang area under hot tropical climate. Numerical results showed that single reflection was the major element in thermal concentration. The concentration ratio was the highest at the upper part of the receiver and decreased towards its lowest region. The results indicated that the concentration ratio and solar flux density of collector deteriorated substantially during the off solar noon hour. According to the simulation finding, during 08:00 and 16:00 solar time under clear sky of tropics, the percentage reduction of solar flux density was over 82% at all points of the receiver. This undesirable performance of collector was due to atmospheric attenuation and cosine effect of the stationary collector. The simulated radiation contour mapping of the receiver supported the result. The performance of the collector was impaired by the cloudy tropical climate that reduced the availability of solar radiation. It was discovered that the expected highest performance of collector at solar noontime might not be fully valid in the real tropics sky. Results showed that global radiation with less than 400 W/m2 had no significant contribution on the thermal concentration at receiver. Besides, it was observed that the elevation of solar angular deviation promoted a very poor collector performance, which agreed to the predicted results. The numerical model was compared with the experimental data; and were in agreement. In general, the temperature profiles from the experiment had the similar trend patterns to the predicted solar flux density from the simulation model. The additional experiments confirmed the simulation results.